Answer:
28.3
Step-by-step explanation:
Use the Pythagorean Theorem to solve for the answer. 10^2 + x^2 = 30^2
Answer:
7 , 8 , 9
Step-by-step explanation:
Assume three consecutive number are,
x , (x+1) , (x+2)
Multiplied by 2 ,3 and 4 respectively
2x , 3(x + 1) , 4(x + 2)
Sum of all = 74
So,
2x + 3(x + 1) + 4(x + 2) = 74
2x + 3x + 3 + 4x + 8 = 74
9x + 11 = 74
9x = 63
x = 7
So,
x , (x+1) , (x+2)
7 , (7+1) , (7+2)
7 , 8 , 9
To write this equation in simplest form, we simply need to combine all like terms. The like terms in this particular expression are the terms with an n-variable and the terms with no variable. So we can combine them to simplify our expression.
5n - 6 + n - 1
First step, we can reorder our terms so that like terms are near each other
5n + n - 6 - 1
Now we can combine easily
(5n + n) - (6 - 1)
6n - 5
And that is your simplified expression.
5n - 6 + n - 1 in simplest form is 6n - 5.
Hope that helped! =)